Transcriptional Inhibition of the Human Papilloma Virus Reactivates Tumor Suppressor p53 in Cervical Carcinoma Cells - Budanov, Andrei; Kochetkov, D.V.; Ilyinskaya, G.V.; Komarov, P.G.; Strom, E.; Agapova, L.S; Ivanov, A.V.; Frolova, E.I.; Chumakov, P.M. (My University, 2007)
Inactivation of tumor suppressor p53 accompanies the majority of human malignancies. Restoration of p53 function causes death of tumor cells and is potentially suitable for gene therapy of cancer. In cervical carcinoma, human papilloma virus (HPV) E6 facilitates proteasomal degradation of p53. Hence, a possible approach to p53 reactivation is the use of small molecules suppressing the function of viral proteins. HeLa cervical carcinoma cells (HPV-18) with a reporter construct containing the β-galactosidase gene under the control of a p53-responsive promoter were used as a test system to screen a library of small molecules for restoration of the transcriptional activity of p53. The effect of the two most active compounds was studied with cell lines differing in the state of p53-dependent signaling pathways. The compounds each specifically activated p53 in cells expressing HPV-18 and, to a lesser extent, HPV-16 and exerted no effect on control p53-negative cells or cells with the intact p53-dependent pathways. Activation of p53 in cervical carcinoma cells was accompanied by induction of p53-dependent CDKN1 (p21), inhibition of cell proliferation, and induction of apoptosis. In addition, the two compounds dramatically decreased transcription of the HPV genome, which was assumed to cause p53 reactivation. The compounds were low-toxic for normal cells and can be considered as prototypes of new anticancer drugs.
PUBLISHED
Keywords: p53; Human papilloma virus; Cervical carcinoma; HeLa cells; Chemical library; Transcriptional reporter construct; β-galactosidase; Suppression of cell proliferation; Apoptosis; Ageing; Cancer; CANCER; Age-related disability; Health